Comprehension and production of emotional words in communication-related disorders: A Narrative Review - Martínez-Tomás, Celia; Baciero, Ana; Hinojosa, español (Revista de Investigación en Logopedia, 2025)
Language and emotion processing have typically been studied separately. Nonetheless, the interest on how semantic emotional features affect linguistic processing has increased in recent years. Research has shown that emotion plays a role in all components of language understanding and expression. This is especially important for individuals with communication-related disorders, who often experience difficulties in both language processing and emotional understanding. This review synthesizes what is known about the processing and use of emotional words in individuals with impairments that affect their communication. We focused on Developmental Language Disorder (DLD), Aphasia, and Autism Spectrum Disorder (ASD). This research can be of help to deepen our understanding of emotional language processing in general, as well as the specific challenges faced by these populations. The review underscores the importance of applying this knowledge to improve assessment methods and therapeutic strategies tailored to individuals with communication-related disorders, while also calling for further research to fully understand the complexities involved. Finally, we underscore the need to conduct research on individuals with writing and reading disorders like developmental dyslexia since evidence on the processing of emotional language in these populations is still marginal.